Gender equality in the government water, sanitation, and hygiene workforce in Indonesia: an analysis through the Gender at Work framework. Issue 1 (1st January 2021) - Soeters, Simone; Siscawati, Mia; Ratnasari,; Anggriani, Septiani; Nailah,; Willetts, Juliet
ABSTRACT: Gender inequality remains a persistent challenge in workforces globally, with the water, sanitation, and hygiene (WASH) workforce no exception. This paper aimed to investigate gender dynamics in the Indonesian government WASH workforce at national and subnational levels and evolve conceptual foundations for this type of study. The Gender at Work framework (Rao, A., J. Sandler, D. Kelleher, and C. Miller. 2016. Gender at Work: Theory and Practice for 21st Century Organizations . London: Routledge), provided a framing to support critical examination of power relations embedded in institutions and communities. In-depth interviews were undertaken with 52 government employees in the districts of Sumbawa and Manggarai and two national ministries. The findings identified four important themes which hinder or support gender equality in the Indonesian government WASH workforce: (a) career progression, continued education, and professional ambitions; (b) gender equality and gendered social dynamics in the workplace; (c) family and institutional support; and (d) gender-based violence and safety in the workplace. Our findings also generated insights on intersectional aspects, including people of different ethnic origins, pointing to the need to explicitly account for these in frameworks such as the Gender at Work framework. Through the identification and consideration of 'gendered substructures' this research provides a basis to promote greater equality in the WASH workforce.